Development of CTL (Contextual Teaching and Learning)-Based E-Comic Media for Teaching Cultural Diversity to Fourth-Grade Elementary School Students - R. Angga Bagus Kusnanto; Sindy Aulia; Tio Gusti Satria (Yayasan Citra Dharma Cindekia, 2026)
This study aimed to develop a Contextual Teaching and Learning (CTL)-based e-comic for cultural diversity learning in grade IV and to determine its validity, practicality, and effectiveness. The study employed the ADDIE research and development model, consisting of analysis, design, development, implementation, and evaluation. The product integrated contextual learning activities with local cultural elements and was evaluated by media, language, and subject-matter experts. Practicality was examined through teacher responses and one-to-one and small-group trials, whereas effectiveness was assessed using pretest and posttest scores from 32 students. The expert validation yielded an average score of 96%, indicating that the product was highly valid. The practicality assessment reached 95%, indicating that the media was highly practical. Students’ mean score increased from 54.49 on the pretest to 82.52 on the posttest, with an N-gain of 0.62 in the moderate category. These findings indicate that the CTL-based e-comic is valid, practical, and effective for supporting meaningful cultural diversity learning in elementary school.